A qualitative assessment and ethical evaluation of 'no choice' in parent kidney donors. (24th May 2012) - Burnell, P; Hulton, SA; Draper, H
Abstract : Aims: There is a paucity of UK literature on parental live kidney donors and debate about whether a parent can make a voluntary decision to be a live donor for their child. Accordingly, the purpose of this paper is two-fold: (1) to explore the contention that parents have 'no choice' but to donate a kidney if their child needs one, using ethical analysis and original qualitative data, and (2) to use this exploration to assess parental voluntariness in parent-child kidney donation. Methods: Data were gathered as part of a wider study exploring parental experiences of consenting for referral for consideration of live donation to their child at a UK inner-city specialist children's hospital. Parents who donated a kidney to their child between September 2006 and December 2010, and consented for referral at their child's hospital, were invited by letter to participate. There were nineteen potential participants. Individual interviews were conducted with seven father-donors and three mother-donors. Qualitative analysis largely followed conventional content analysis. An empirical bioethics approach (using a simple thematic analysis) facilitated consideration of ethical issues. Results: Of the data analysed, three main themes are presented: (1) Motivations for donation; The primary motivation was 'being a parent'. Parents expressed this in terms of parental love and concern, rather than obligation. (2) A parent's decision; Generally, participants considered parents in their situation to have a choice. 80% of participants said they would respect a parent who decided, for whatever reason, not to donate. (3) Certainty; Participants conveyed certainty about their decision to donate and viewed live donation as a positive opportunity. The pressure typically came from participants not knowing whether they were a tissue match. Conclusion: Voluntariness is not compromised where donation is motivated by the parent's values. Our results suggest 'no choice' might better describe situations where parents are unable to donate to their children. The extent to which these results are generalisable remains to be shown, however they suggest that when discussing live donation with parents, health professionals need not be unduly nervous about creating a situation where parental voluntariness is compromised by an internal pressure to donate.